Uji Toksisitas Ekstrak Etanol Kulit Batang Soni (Dillenia serrata Thunb) dengan Metode BSLT (Brine Shrimph Lethality Test) - Maryani; Nurlansi; Nasrudin (Sains: Jurnal Kimia dan Pendidikan Kimia, 2022)
Toxicity Test of Soni (Dillenia serrata Thunb) Bark Bark Ethanol Extract has been conducted using the BSLT (Brine Shrimph Lethality Test) Method. This study aims to determine the toxicity of the Soni (Dillenia serrata Thunb) Bark Ethanol Extract extract. The secondary metabolites contained in the ethanol extract of Batang Soni Bark were determined by the phytochemical method, while the toxicity of the extract was determined by the BSLT method. Soni bark used is dry soni bark that has been mashed. A total of 500 g of soni bark was macerated for 3x24 hours with 96% ethanol solvent that had been distilled. The filtrate was then collected and concentrated to obtain a thick extract of 80.05 g. Soni bark ethanol extract was tested for phytochemical and toxicity. Phytochemical test results showed that the ethanolic extract of soni bark contains flavonoids, steroids, triterpenoids, polyphenols, and tannins. Soni bark ethanol extract has a very strong toxicity with an LC50 value of 18.62 ppm